Digital Resources for Ancient Languages - Alterman, Mark (Stone-Campbell journal, 2007)
Serious study of ancient languages was essential to the early leaders of the Stone-Campbell Restoration Movement. Today, study of ancient languages can be enhanced by using multimedia resources. Various resources are surveyed, mostly Internet-based. Resources are included for Hebrew, Greek, Latin, Medieval Italian, Coptic, Egyptian, Aramaic, Arabic, Sanskrit, Akkadian, and Ugaritic. Comments relating to the pronunciation and reading of ancient texts are interspersed in the descriptions.